“Protection for Sale” in a Developing Country: Democracy vs. Dictatorship - Mitra, Devashish; Thomakos, Dimitrios D.; Ulubaşoğlu, Mehmet A. (The Review of Economics and Statistics, 2002)
For a “genuine” small open economy that has experienced both dictatorship and democracy, we find support for the predictions of the Grossman-Helpman (1994) “Protection for Sale” model. In contrast to previous studies, we use various protection measures (including tariffs, the direct measure of the theoretical model) and perform both single-year and panel regressions. Using Turkish industry-level data, the government's weight on welfare is estimated to be much larger than that on contributions. More importantly, we find that this weight is generally higher for the democratic regime than for dictatorship.